2016
DOI: 10.5551/jat.34462
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of the Aryl Hydrocarbon Receptor (AhR) in Indoxyl Sulfate-Induced Vascular Inflammation

Abstract: Aim:The aryl hydrocarbon receptor (AhR), a ligand-inducible transcription factor mediating toxic effects of dioxins and uremic toxins, has recently emerged as a pathophysiological regulator of immune-inflammatory conditions. Indoxyl sulfate, a uremic toxin, is associated with cardiovascular disease in patients with chronic kidney disease and has been shown to be a ligand for AhR. The aim of this study was to investigate the potential role of AhR in indoxyl sulfate-induced leukocyte -endothelial interactions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 61 publications
1
78
2
Order By: Relevance
“…Since IS was identified as a potent endogenous ligand for the aryl hydrocarbon receptor (AhR) (16), an increasing number of studies have focused on the biologic role of the AhR pathway in the pathogenesis of CKD (13,(17)(18)(19). However, the mechanisms underlying the IS-mediated AhR pathway have mainly been explored in renal cells, vascular endothelial cells (VECs), and vascular smooth muscle cells.…”
mentioning
confidence: 99%
“…Since IS was identified as a potent endogenous ligand for the aryl hydrocarbon receptor (AhR) (16), an increasing number of studies have focused on the biologic role of the AhR pathway in the pathogenesis of CKD (13,(17)(18)(19). However, the mechanisms underlying the IS-mediated AhR pathway have mainly been explored in renal cells, vascular endothelial cells (VECs), and vascular smooth muscle cells.…”
mentioning
confidence: 99%
“…At the same time, it has been proven that IS-mediated leukocyte–endothelial interactions affect E/P-selectins expression [60]. Similarly, the progression of vascular damage in essential hypertension is associated with a rise in circulating levels of P-selectins and, to a lesser extent, E-selectins.…”
Section: Discussionmentioning
confidence: 99%
“…Activating AHR promotes both atherosclerosis in mice with an apolipoprotein E deficiency,37 and leukocyte endothelial interaction induced by TNF‐α 38. The findings of clinical studies have suggested that AHR contributes to thrombotic complications in patients with chronic kidney disease 39, 40.…”
Section: Discussionmentioning
confidence: 99%